Free Range Hens Use the Range More When the Outdoor Environment Is Enriched - Nagle, T. A. D. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
To evaluate the role of using forage, shade and shelterbelts in attracting birds into the range, three trials were undertaken with free range layers both on a research facility and on commercial farms. Each of the trials on the free range research facility in South Australia used a total of 120 laying hens (Hyline Brown). Birds were housed in an eco-shelter which had 6 internal pens of equal size with a free range area adjoining the shelter. The on-farm trials were undertaken on commercial free range layer farms in the Darling Downs in Southeast Queensland with bird numbers on farms ranging from 2,000–6,800 hens. The first research trial examined the role of shaded areas in the range; the second trial examined the role of forage and the third trial examined the influence of shelterbelts in the range. These treatments were compared to a free range area with no enrichment. Aggressive feather pecking was only observed on a few occasions in all of the trials due to the low bird numbers housed. Enriching the free range environment attracted more birds into the range. Shaded areas were used by 18% of the hens with a tendency (p = 0.07) for more hens to be in the paddock. When forage was provided in paddocks more control birds (55%) were observed in the range in morning than in the afternoon (30%) while for the forage treatments 45% of the birds were in the range both during the morning and afternoon. When shelterbelts were provided there was a significantly (p<0.05) higher % of birds in the range (43% vs. 24%) and greater numbers of birds were observed in areas further away from the poultry house. The results from the on-farm trials mirrored the research trials. Overall 3 times more hens used the shaded areas than the non shaded areas, with slightly more using the shade in the morning than in the afternoon. As the environmental temperature increased the number of birds using the outdoor shade also increased. Overall 17 times more hens used the shelterbelt areas than the control areas, with slightly more using the shelterbelts in the afternoon than in the morning. Approximately 17 times more birds used the forage areas compared to the control area in the corresponding range. There were 8 times more birds using a hay bale enriched area compared to the area with no hay bales. The use of forage sources (including hay bales) were the most successful method on-farm to attract birds into the range followed by shelterbelts and artificial shade. Free range egg farmers are encouraged to provide pasture, shaded areas and shelterbelts to attract birds into the free range.